2005
DOI: 10.1099/mic.0.28159-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence assays for F-pili and their application

Abstract: Conjugative pili are extracellular filaments elaborated by Gram-negative bacteria expressing certain type IV secretion systems. They are required at the earliest stages of conjugal DNA transfer to establish specific and secure cell-cell contacts. Conjugative pili also serve as adsorption organelles for both RNA and DNA bacteriophages. Beyond these facts, the structure, formation and function of these filaments are poorly understood. This paper describes a rapid, quantitative assay for F-pili encoded by the F p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…We showed that fluorescent R17 bacteriophage binding to fixed E. coli Fϩ cells could be used to identify F-pili (23). We have now extended this approach to visualize filament dynamics on live cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that fluorescent R17 bacteriophage binding to fixed E. coli Fϩ cells could be used to identify F-pili (23). We have now extended this approach to visualize filament dynamics on live cells.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli K-12 strains HfrH and AE2386/JCFL0 were from the authors' strain collection and have been described (23). The strains expressed the cytoplasmic, IPTG-inducible fluorescent marker DsRed Express (31).…”
Section: Methodsmentioning
confidence: 99%
“…F-pili were purified from the supernatant fraction by two cycles of isopycnic sedimentation in sucrose gradients (density range = 1.16 to 1.29 g/mL). Fractions at ∼1.2 g/mL were examined by fluorescence microscopy for F-pili28 and by SDS gel electrophoresis for purity (where preparations were judged to be >90% F-pilin). Images of frozen-hydrated F-pili were collected on a Tecnai 20 field emission gun microscope at 200 keV.…”
Section: Figuresmentioning
confidence: 99%
“…The titer was 1.02 ϫ 10 14 PFU/ml. Phage were labeled with Alexa Fluor 488 (Invitrogen) as described previously (55), except that phages were harvested from a discontinuous CsCl gradient at a of ϳ1.45 g/ml and the addition of glycerol was omitted. After labeling, phage were treated with chloroform to dissolve detached R1-16 pili still present in the preparation, dialyzed in P buffer, and then filtered through a 0.2-m filter and stored at 4°C.…”
Section: Figmentioning
confidence: 99%